Noncovalent Carbon‐Bonding Interactions in Proteins. (12th November 2018) - Mundlapati, V. Rao; Sahoo, Dipak Kumar; Bhaumik, Suman; Jena, Subhrakant; Chandrakar, Amol; Biswal, Himansu S.
Abstract: Carbon bonds (C‐bonds) are the highly directional noncovalent interactions between carbonyl‐oxygen acceptors and sp 3 ‐hybridized‐carbon σ‐hole donors through n→σ* electron delocalization. We have shown the ubiquitous existence of C‐bonds in proteins with the help of careful protein structure analysis and quantum calculations, and have precisely determined C‐bond energies. The importance of conventional noncovalent interactions such as hydrogen bond (H‐bonds) and halogen bond (X‐bonds) in the structure and function of biological molecules are well established, while carbon bonds C‐bonds have still to be recognized. We have shown that C‐bonds are present in proteins, contribute enthalpically to the overall hydrophobic interaction and play a significant role in the photodissociation mechanism of myoglobin and the binding of nucleobases to proteins.